Characterization of the Methylthioadenosine Phosphorylase Polymorphism rs7023954 - Incidence and Effects on Enzymatic Function in Malignant Melanoma - Limm, Katharina; Dettmer, Katja; Reinders, Joerg; Oefner, Peter J.; Boßerhoff, Anja Katrin (PLoS ONE, 2016)
Deficiency of methylthioadenosine phosphorylase (MTAP) supports melanoma development and progression through accumulation of its substrate 5'-methylthioadenosine (MTA), which leads amongst others to a constitutive inhibition of protein arginine methyltransferases (PRMTs) and activation of the transcription factor AP-1 via the receptor ADORA2B. Genetic association studies have also suggested that genetic polymorphism in MTAP may modulate the risk of melanoma. Here, we investigated the only globally common non-synonymous single nucleotide polymorphism (SNP) reported to date for MTAP. The SNP rs7023954 is located in exon 3 (c.166G>A), and leads to the conservative substitution of one branched-chain amino acid residue (valine) for another (isoleucine) at position 56 (p.Val56Ile). Whereas genotype frequencies in normal and primary melanoma tissues or cell lines were in Hardy-Weinberg equilibrium based on cDNA amplicon sequencing, a marked (P = 0.00019) deviation was observed in metastatic melanoma tissues and cell lines due to a deficit of heterozygotes. Enzyme assays conducted on the co-dominantly expressed alleles revealed no difference in the conversion rate of MTA to adenine and 5-methylthioribose-1-phosphate, indicating that this known enzymatic activity does not modulate the tumor suppressive function of MTAP.
EVALuna2:4733